Obstetrics and Gynaecology for Finals, DRCOG and MRCOG : A Revision Guide - Rymer, Janice; Smith, Norman; Taylor and Francis (Boca Raton, FL : Taylor and Francis, an imprint of CRC Press, 2017)
This examination and revision guide comprehensively tests knowledge at all levels in obstetrics and gynaecology. The wide-ranging sample questions have detailed answers to provide proper explanation and aid understanding, and the variety of question formats prepares students for all possibilities in the examination. The best of five question format is ideal for DRCOG candidates, the EMQs prepare the MRCOG candidates, and the MCQs will test both DRCOG and MRCOG candidates. The book is also highly recommended for undergraduates preparing for their finals, who will welcome the sample best of fives and EMQs now that essays and short answer questions are becoming a thing of the past.
Contents: MCQ Paper 1. MCQ Paper 2. MCQ Paper 3. MCQ Paper 4. Single Best Answers Obstetrics. Single Best Answers Gynaecology. Extended Matching Questions Obstetrics. Extended Matching Questions Gynaecology.
Includes bibliographical references and index.
Also available in print format.
Keywords: Obstetrics -- Examinations, questions, etc; Gynecology -- Examinations, questions, etc; Gynecology; Obstetrics; MEDICAL / Gynecology & Obstetrics; Electronic books